2023
DOI: 10.1200/jco.2023.41.6_suppl.355
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a multi-institutional nomogram of outcomes for PSMA-PET–based salvage radiotherapy in recurrent prostate cancer.

Abstract: 355 Background: We aimed to develop and to validate a multi-institutional nomogram of outcomes for PSMA-PET based salvage radiotherapy (sRT) following radical prostatectomy (RP) for patients with recurrent or persistent prostate cancer (PCa). Methods: Data from patients with a detectable post-RP prostate-specific antigen (PSA) treated with sRT with or without concurrent androgen-deprivation therapy (ADT) were obtained from 11 academic institutions from 5 countries. All patients had a PSMA-PET scan prior sRT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In addition, the utility of PSMA-PET in the post-operative space for BCR is evolving with no clear guidelines on whether ADT should be incorporated into treatment depending on a positive or negative PSMA-PET scan. [18][19][20] However, if there is macroscopic disease detected, addition of ADT should generally be considered.…”
Section: Guideline Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the utility of PSMA-PET in the post-operative space for BCR is evolving with no clear guidelines on whether ADT should be incorporated into treatment depending on a positive or negative PSMA-PET scan. [18][19][20] However, if there is macroscopic disease detected, addition of ADT should generally be considered.…”
Section: Guideline Statementsmentioning
confidence: 99%
“…3,17 Thus, for patients with highrisk features requiring salvage RT, clinicians may extend ADT duration to 18 to 24 months while data matures from the RADICALS-HD trial (NCT00541047), which directly compares short-term versus long-term ADT with salvage RT. 19. In patients with BCR following RP undergoing salvage RT with ADT, clinicians may use expanded radiation fields that include the regional lymph nodes.…”
Section: Guideline Statementsmentioning
confidence: 99%
“…Metastases to lymph nodes detected by PSMA PET are risk factors for poor outcomes in risk prediction nomograms being developed for salvage radiotherapy. 50 A small study of choline PET in the setting of BCR for salvage radiotherapy showed choline PET changed the extent of RT in 13% of patients. However, this was a small (37 patients) retrospective study with no control group.…”
Section: Pet Radiotracers In Salvage Radiotherapy and Oligometastatic...mentioning
confidence: 99%